Intensity mapping cross-correlations II: HI halo models including shot noise. Issue 1 (22nd November 2018) - Wolz, L; Murray, S G; Blake, C; Wyithe, J S
ABSTRACT: H i intensity mapping data traces the large-scale structure matter distribution using the integrated emission of neutral hydrogen gas (H i ). Cross-correlation of the intensity maps with optical galaxy surveys can mitigate foreground and systematic effects, but has been shown to significantly depend on galaxy evolution parameters of the H i and the optical sample. Previously, we have shown that the shot noise of the cross-correlation scales with the H i content of the optical samples, such that the shot noise estimation infers the average H i masses of these samples. In this paper, we present an adaptive framework for the cross-correlation of H i intensity maps with galaxy samples using our implementation of the halo model formalism which utilizes the halo occupation distribution of galaxies to predict their power spectra. We compare two H i population models, tracing the spatial halo and the galaxy distribution, respectively, and present their auto- and cross-power spectra with an associated galaxy sample. We find that the choice of the H i model and the distribution of the H i within the galaxy sample have little impact for the shape of the auto- and cross-correlations, but significantly affects the measured shot noise amplitude of the estimators, a finding we confirm with simulations. We demonstrate parameter estimation of the H i halo occupation models and advocate this framework for the interpretation of future experimental data, with the prospect of determining the H i masses of optical galaxy samples via the cross-correlation shot noise.